IPCC "Summary for policymakers" in TAR: Do its results give a support always adequate to the urgencies of Kyoto global negotiations? - Maurizio Michelini (Fondazione Eni Enrico Mattei (FEEM), 2001)
One of the most important reasons by which Kyoto negotiations had suffered a setback at the COP 6 conference may be the unsatisfactory state about the previsions of Global Warming. This lack of knowledge may have such an influence on the formation of human opinion that we cannot to be amazed if the policymakers did not find a common mind to proceed in the fulfilment of the Kyoto protocol. Of course, the uncertainties in the scientific knowledge cannot be avoided or attributed to something in particular. However the presentation of the complex results obtained by IPCC during many years of work has not received the right importance. In our opinion the Summary's description of the Global Warming by means of simulations stopped at year 2100 does not appear to be suitable to induce a correct risk perception. A preliminary simulation is described which may clarify this concept.
Keywords: O19; 330; Kyoto Protocol; world energy scenarios; CO2 global emissions; Klimawandel; Internationale Umweltpolitik; Luftverschmutzung; Treibhausgas-Emissionen; Welt